Cyclic Nucleotide–Gated Channels Colocalize with Adenylyl Cyclase in Regions of Restricted Camp Diffusion - Rich, Thomas C. (The Rockefeller University Press, 2000)
Cyclic AMP is a ubiquitous second messenger that coordinates diverse cellular functions. Current methods for measuring cAMP lack both temporal and spatial resolution, leading to the pervasive notion that, unlike Ca(2+), cAMP signals are simple and contain little information. Here we show the development of adenovirus-expressed cyclic nucleotide–gated channels as sensors for cAMP. Homomultimeric channels composed of the olfactory α subunit responded rapidly to jumps in cAMP concentration, and their cAMP sensitivity was measured to calibrate the sensor for intracellular measurements. We used these channels to detect cAMP, produced by either heterologously expressed or endogenous adenylyl cyclase, in both single cells and cell populations. After forskolin stimulation, the endogenous adenylyl cyclase in C6-2B glioma cells produced high concentrations of cAMP near the channels, yet the global cAMP concentration remained low. We found that rapid exchange of the bulk cytoplasm in whole-cell patch clamp experiments did not prevent the buildup of significant levels of cAMP near the channels in human embryonic kidney 293 (HEK-293) cells expressing an exogenous adenylyl cyclase. These results can be explained quantitatively by a cell compartment model in which cyclic nucleotide–gated channels colocalize with adenylyl cyclase in microdomains, and diffusion of cAMP between these domains and the bulk cytosol is significantly hindered. In agreement with the model, we measured a slow rate of cAMP diffusion from the whole-cell patch pipette to the channels (90% exchange in 194 s, compared with 22–56 s for substances that monitor exchange with the cytosol). Without a microdomain and restricted diffusional access to the cytosol, we are unable to account for all of the results. It is worth noting that in models of unrestricted diffusion, even in extreme proximity to adenylyl cyclase, cAMP does not reach high enough concentrations to substantially activate PKA or cyclic nucleotide–gated channels, unless the entire cell fills with cAMP. Thus, the microdomains should facilitate rapid and efficient activation of both PKA and cyclic nucleotide–gated channels, and allow for local feedback control of adenylyl cyclase. Localized cAMP signals should also facilitate the differential regulation of cellular targets.